Comparison between collet and cooking extrusions on physicochemical properties of whole grain barley. Issue 3 (9th September 2016) - Chang, Chiawei; Lin, Jenshinn
Abstract: The experiment was designed to study physicochemical properties of collet and cooking extrudates of hulless barley with different extrusion parameters: feed moisture content, screw speed, and temperature. The lightness ( L *) and total color difference (Δ E ) values were increased with increasing screw speed and decreasing feed moisture content in collet extrudates. The maximum shear force (MSF) decreased with the increase of temperature in collet extrusion, while MSF was increased with increasing temperature under same feed moisture content condition in cooking extrusion. The degree of gelatinization (DG) showed tendency to be increased at higher feed moisture content, lower screw speed, and higher extrusion temperature. Scanning electron microscope observation of extrudates with the lowest MSF, which was obtained from collet extrusion at 12% feed moisture content, 400 rpm screw speed, and 110 °C showed less dense structure and less un‐gelatinized starch, compared to collect extrudates that had the highest MSF. Soluble dietary fiber of hulless barley (7.84%) was increased after collet extrusion up to 0.34% and decreased after cooking extrusion up to 0.92%. Feed moisture content was the most influencing variable on L *, Δ E, MSF, and DG values of collet extrudates, whereas temperature was the most influencing variable on dietary fiber content. Practical applications: The results obtained are useful for the food industry for value addition of hulless barley by extrusion cooking. Parameters (feed moisture content, screw speed and temperature) and extrusion methods (collet or cooking extrusions) needed to produce extrudates with expected psychochemical properties can be predicted from this study.